Teachers' Perception of Smartboard Technology Innovation As A Support for Learning Change in Private Junior High School Pab 21 Pematang Johar - Lathifatun Nisa Hutabarat; Rustam Rustam (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
This study aims to analyze teachers' perceptions of Smartboard technology innovation as a support for instructional transformation at SMP Swasta PAB 21 Pematang Johar. Using a qualitative descriptive approach, data were collected through observation, semi-structured interviews with eight purposively selected teachers, and documentation. The findings indicate that teachers' perceptions are influenced by perceived usefulness, ease of use, and professional and psychological readiness. Smartboard is considered effective in enhancing visual learning quality and student engagement; however, its utilization remains suboptimal due to limited technological competence and infrastructural constraints. Furthermore, implementation is still at an early stage primarily at substitution and augmentation levels rather than transformative learning. The successful implementation of this technology depends on strengthening teacher competencies, institutional support, and adaptive readiness toward digital-based learning transformation.